(untitled) - Vapnek, Jessica (Rome, 2005)
The increasing globalization of food trade and the harmonization of food standards and food safety rules have led to significant changes in the international and national regulatory frameworks for food. There is an increasing recognition of the need to integrate and improve coordination of regulatory activities among national and international bodies for better protection of human, animal and plant life and health without creating unnecessary barriers to trade. In addition, catastrophic outbreaks of food-borne disease have sparked increasing attention to the regulatory frameworks for food safety and food trade in the global arena. These developments have given rise to new legislative needs. National regulatory frameworks have to be adjusted to meet international and regional obligations, while the distribution of responsibilities for the food sector requires rigorous review. The present text draws on FAO's experience in providing technical assistance to governments developing new food laws and regulations, setting out and examining the many elements of the nationalsystem which should be taken into account in a comprehensive review of national regulatory frameworks for food. Towards that end, the text offers concrete recommendations for the preparation of a basic national food law, including three variants of a new model food law.
Keywords: Food law and legislation